Thrombocytopenia, neutropenia, ulcerative dermatitis and haemarthrosis in a neonatal foal - Preez, S.; Hughes, K. J. (Equine veterinary education, 2018)
Summary A 3‐day‐old Standardbred filly, born from a multiparous mare, was presented for assessment of limb swellings and reduced appetite. Physical examination revealed tachycardia, multifocal petechial and ecchymotic haemorrhages, stiff gait, polysynovial effusion, as well as erosions, multifocal crusting and erythema of the skin. Laboratory examinations revealed adequate transfer of passive immunity, marked thrombocytopenia, moderate neutropenia and anaemia. Aerobic bacterial blood culture was negative. Sanguineous fluid, consistent with haemarthrosis, was obtained by synoviocentesis. The foal was successfully managed with the administration of blood transfusions, an immunosuppressive regimen of corticosteroid medication, systemic antimicrobial medication and supportive care and recovered uneventfully. This report describes a neonatal foal with marked thrombocytopenia and signs of coagulopathy, neutropenia and ulcerative dermatitis consistent with a previously described syndrome. This case emphasises that alloimmune disease should be considered in neonatal foals with haemostatic disturbances or unexplained cytopenia.